Genetic associations with brain cortical thickness in multiple sclerosis. (5th March 2015) - Matsushita, T.; Madireddy, L.; Sprenger, T.; Khankhanian, P.; Magon, S.; Naegelin, Y.; Caverzasi, E.; Lindberg, R. L. P.; Kappos, L.; Hauser, S. L.; Oksenberg, J. R.; Henry, R.; et al.
Abstract: Multiple sclerosis (MS) is characterized by temporal and spatial dissemination of demyelinating lesions in the central nervous system. Associated neurodegenerative changes contributing to disability have been recognized even at early disease stages. Recent studies show the importance of gray matter damage for the accrual of clinical disability rather than white matter where demyelination is easily visualized by magnetic resonance imaging (MRI). The susceptibility to MS is influenced by genetic risk, but genetic factors associated with the disability are not known. We used MRI data to determine cortical thickness in 557 MS cases and 75 controls and in another cohort of 219 cases. We identified nine areas showing different thickness between cases and controls (regions of interest, ROI) (eight of them were negatively correlated with Kurtzke's expanded disability status scale, EDSS) and conducted genome‐wide association studies (GWAS) in 464 and 211 cases available from the two data sets. No marker exceeded genome‐wide significance in the discovery cohort. We next combined nominal statistical evidence of association with physical evidence of interaction from a curated human protein interaction network, and searched for subnetworks enriched with nominally associated genes and for commonalities between the two data sets. This network‐based pathway analysis of GWAS detected gene sets involved in glutamate signaling, neural development and an adjustment of intracellular calcium concentration. We report here for the first time gene sets associated with cortical thinning of MS. These genes are potentially correlated with disability of MS. Abstract : Common genetic variation is associated with cortical thickness in multiple sclerosis (MS) patients. Here we performed GWA on two independent cohorts of patients ( n = 675 in total). While no marker exceeded genome‐wide significance, protein interaction based network analysis identified pathways involved in glutamate signaling, neural development and intracellular calcium concentration as significantly associated with cortical thickness in MS.